Company Value Model for the 20 Largest Market Capitalizations on the Indonesian Stock Exchange - Luqman Hakim; Arum Indrasari; Rosdiana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study is to address gaps in previous research and explore a phenomenon where institutional ownership historically hasn't been concerned with leverage as a risk factor. Contrary to this trend, our findings indicate that leverage plays a crucial role for institutional ownership within the ownership structure variable. Higher institutional ownership levels tend to increase company leverage, facilitating expansion. Leverage, being a risk factor, is pivotal for investors in the capital market due to its implications for earnings and returns. This research employs a descriptive quantitative approach with multiple linear regression analysis using panel data from twenty large-market-cap companies listed on the Indonesia Stock Exchange (IDX). Our model seeks to optimize Firm Value by integrating Leverage as an intervening variable across two research models. In the first model, Ownership Structure effectively explains the impact on Leverage, aligning with established theories. However, contrary to theory, Liquidity does not significantly influence Leverage in this context. In the second model, Ownership Structure remains influential in explaining Firm Value, whereas Liquidity shows contrasting results. Additionally, Leverage operates as an intervening variable mediating Firm Value. These findings are intended to guide public companies in maximizing their Firm Value effectively